2010
DOI: 10.1111/j.1752-4598.2010.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

A chronosequence of understorey parasitic wasp assemblages in secondary broad‐leaved forests in a Japanese ‘satoyama’ landscape

Abstract: 1. To infer the effects of forest aging on the abundance, genus richness and diversity, and genus composition of understorey parasitoids, we investigated the assemblages of braconids collected in Malaise traps in a chronosequence of secondary broad-leaved forests (4-128 years old) in the satoyama landscape in the cooltemperate region of central Honshu, Japan.2. Multivariate linear regression analysis indicated that the abundance of braconid parasitoids was affected by forest age (time since clear-cutting) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…Throop and Lerdau [56] confirmed the assumption of a positive effect of high nitrogen content on the individual performance of sap-sucking insects and their population levels and Gossner et al [57] proposed similar mechanisms for the higher percentage of sap-sucking Heteroptera in young oak stands on former agricultural fields compared to forest sites due to differences in plant stress. Maleque et al [58] found a general decrease of understorey insect herbivores with forest age which was attributed to the general decrease in forest floor vegetation with stand age. In our study, plant diversity positively affected most herbivores, among these miners, and thus plant diversity might partly explain observed patterns ( Table 3 , see also below).…”
Section: Discussionmentioning
confidence: 97%
“…Throop and Lerdau [56] confirmed the assumption of a positive effect of high nitrogen content on the individual performance of sap-sucking insects and their population levels and Gossner et al [57] proposed similar mechanisms for the higher percentage of sap-sucking Heteroptera in young oak stands on former agricultural fields compared to forest sites due to differences in plant stress. Maleque et al [58] found a general decrease of understorey insect herbivores with forest age which was attributed to the general decrease in forest floor vegetation with stand age. In our study, plant diversity positively affected most herbivores, among these miners, and thus plant diversity might partly explain observed patterns ( Table 3 , see also below).…”
Section: Discussionmentioning
confidence: 97%
“…However, for parasitoids and host -parasitoid systems evidence for cross-taxon congruence with tree species richness or other coarse measures of habitat heterogeneity is sparse and inconclusive. Depending on the study system, parasitoid abundance and species richness increased [13][14][15], were unrelated [43] or declined [44] with habitat heterogeneity, but no study considered descriptors of PD such as tree MPD. As introduced above, a plant community's PD is a suitable surrogate for overall niche availability and habitat heterogeneity [21,23], and more diverse evolutionary lineages will result in more diverse microhabitats.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the succession series of forest husbandry, there are nine periodic habitat series in forest ecosystems ( Figure 2). First, frequent cutting and thinning of woodlands led to the domination of dwarf pines and coppices, and decreased the occurrence of invasive species and increased forest floor species diversity [49,50]. Second, collecting fallen leaves for fertilizer as well as the regular cutting of deciduous forests supports many species of spring and summer wildflowers, which can survive only when the foliage is thin, and sunlight is able to reach the forest floor.…”
Section: Biodiversity Crisis In Satoyama Landscapementioning
confidence: 99%